Obama's energy policy - Mallinson, R (Oxford Institute for Energy Studies, 2013)
In an interview with Time Magazine in December, President Obama made the bold assertion that ‘[t]he United States is going to be a net exporter of energy because of new technologies and what we’re doing with natural gas and oil.’ Although he did not place a timescale on this prediction or specify what new technologies he meant, his comment reflects a radical shift that has been taking place in US energy policy thinking. The largest single cause of the shift has been the boom in US unconventional oil and gas production over the last six years. Domestic natural gas production is at record levels, averaging 65.9 bcf/d in 2012, while total oil production exceeded the 10 mb/d mark in October, for the first time in over 20 years. The rapid growth in production has led to speculation, in Washington and among market analysts, that the USA might achieve energy independence. No longer relying on imports, particularly from Middle Eastern countries, holds strong political appeal, especially when it offers additional domestic jobs in oil and gas production and an improved balance of trade. However, despite the positive outlook for US production, there are several factors limiting the prospects for America’s energy exports.